1978
DOI: 10.7326/0003-4819-88-5-610
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Myoglobinuria Due to Muscle Carnitine Palmityl Transferase Deficiency

Abstract: Three new cases of carnitine palmityl transferase deficiency are described. The syndrome consists of recurrent attacks of muscle cramps, weakness, malaise, and myoglobinuria. These attacks are especially likely to occur during prolonged exercise after fasting, eating a high-fat diet, or during cold weather. Occasionally after fasting alone, spontaneous muscle breakdown may occur. One patient studied in detail was excessively slow in producing ketones when he fasted. His mylagias and weakness appeared to be all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1979
1979
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…"^,^^ Indirect evidence that the liver may also be involved was derived from fasting experiments showing delayed or decreased formation of ketone bodies. 5,8,25,98,104 Decreased CPT activity (26% of the lowest control value) has been documented in a liver biopsy from the patient of Bertorini et al*…”
Section: Disorders Of Lipid Metabolismmentioning
confidence: 97%
“…"^,^^ Indirect evidence that the liver may also be involved was derived from fasting experiments showing delayed or decreased formation of ketone bodies. 5,8,25,98,104 Decreased CPT activity (26% of the lowest control value) has been documented in a liver biopsy from the patient of Bertorini et al*…”
Section: Disorders Of Lipid Metabolismmentioning
confidence: 97%
“…Other precipitants may include, but are not limited to, infection, fasting, cold, increased fat intake, emotional distress, and certain drugs (Kelly et al, 1989;Kottlors et al, 2001;Reza et al, 1978;Wallace et al, 2001). The clinical features of the adult form have occasionally been reported to occur in childhood, as in the case of a 6-year-old girl who presented with acute muscle weakness, pain, and inability to walk.…”
Section: Clinical and Metabolic Features Of Cpt II Deficiencymentioning
confidence: 99%
“…Hypotheses include lack of enzymatically active protein, partial enzyme deficiency and abnormally regulated enzyme [62]. In previous studies, CPT activities in muscles of patients with CPT II deficiency are reported to be undetectable [30,63,64], reduced [62][63][64][65][66][67][68] or normal [69].…”
Section: Molecular Genetic Aspectsmentioning
confidence: 99%